Bone Morphogenetic Protein 2 Coordinates Early Tooth Mineralization. (July 2018) - Malik, Z.; Alexiou, M.; Hallgrimsson, B.; Economides, A.N.; Luder, H.U.; Graf, D.
Formation of highly organized dental hard tissues is a complex process involving sequential and ordered deposition of an extracellular scaffold, followed by its mineralization. Odontoblast and ameloblast differentiation involves reciprocal and sequential epithelial-mesenchymal interactions. Similar to early tooth development, various Bmps are expressed during this process, although their functions have not been explored in detail. Here, we investigated the role of odontoblast-derived Bmp2 for tooth mineralization using Bmp2 conditional knockout mice. In developing molars, Bmp2LacZ reporter mice revealed restricted expression of Bmp2 in early polarized and functional odontoblasts while it was not expressed in mature odontoblasts. Loss of Bmp2 in neural crest cells, which includes all dental mesenchyme, caused a delay in dentin and enamel deposition. Immunohistochemistry for nestin and dentin sialoprotein (Dsp) revealed polarization defects in odontoblasts, indicative of a role for Bmp2 in odontoblast organization. Surprisingly, pSmad1/5/8, an indicator of Bmp signaling, was predominantly reduced in ameloblasts, with reduced expression of amelogenin ( Amlx ), ameloblastin ( Ambn ), and matrix metalloproteinase ( Mmp20 ). Quantitative real-time polymerase chain reaction (RT-qPCR) analysis and immunohistochemistry showed that loss of Bmp2 resulted in increased expression of the Wnt antagonists dickkopf 1 ( Dkk1 ) in the epithelium and sclerostin ( Sost ) in mesenchyme and epithelium. Odontoblasts showed reduced Wnt signaling, which is important for odontoblast differentiation, and a strong reduction in dentin sialophosphoprotein ( Dspp ) but not collagen 1 a1 ( Col1a1 ) expression. Mature Bmp2 -deficient teeth, which were obtained by transplanting tooth germs from Bmp2 -deficient embryos under a kidney capsule, showed a dentinogenesis imperfecta type II–like appearance. Micro–computed tomography and scanning electron microscopy revealed reduced dentin and enamel thickness, indistinguishable primary and secondary dentin, and deposition of ectopic osteodentin. This establishes that Bmp2 provides an early temporal, nonredundant signal for directed and organized tooth mineralization.